The Comparative Study of Interfering Factors Effect in learning Language - Janfaza, Elenaz; Janfaza, Sulmaz (Mediterranean Journal of Social Sciences, 2012)
In the world scenario communication have an important role within the globalization. But this cannot be successful unlesseducation. As we know all the people are not able to learn foreigner second languages during a long term process so they need to choosean institute as a replacement for schools or university education in order to learn language as short as he/she can. So it is important to choosethe successful institute but how he can choose the successful institute? By which factor he is able to realize this institute? So I decided tostudy on the interfering factors which affect the learning languages process. According to my last paper" Alarm! Language Learning Instituteor sales room" we suppose some factors including: teacher, facilities, student, manager, space, methods, and learning/teaching strategiesin this study in order to evaluate the effect of these factors in learning language as a whole. According to the results the aim of theexaminers of learning language was obligation (15%), the role of the teachers and her/his methodology (53%), the facility of the institutes andschools/universities were 46% and 0% respectively, 92% of teachers of schools and universities just try to teach grammar and structure alonewithout any new methodology.